(untitled) (Anclajes, 2021)
In Fuenzalida (2012), by Chilean writer Nona Fernández, the protagonist embarks on a quest to reconstruct her father’s life and a period of her country’s history. In the novel, the protagonist accesses both histories through other people’s memories and stories. This reassembling entails simultaneously rethinking her private history and the History of Chile. This article proposes a reading on family histories and the meaning of memory, which is indebted to transmitted stories. Like a game of mirrors, in this novel fiction and history combine to give a twist to a well-known topic in Latin American literature.